2013
DOI: 10.1016/j.bbmt.2013.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Infection after Adult Autologous Stem Cell Transplantation: A Multicenter Study of Epidemiology and Risk Factors

Abstract: We sought to describe the epidemiology of Clostridium difficile infection (CDI) among adult recipients of autologous hematopoietic stem cell transplantation (auto HSCT) within the first year after HSCT in centers with variable epidemiology of hyper-toxigenic strains. A multicenter, retrospective nested case-control study was conducted among 873 auto HSCT recipients at Johns Hopkins Hospital (JHH, Baltimore, MD) and Hôpital Maisonneuve-Rosemont (HMR, Montreal, Canada) between 1/2003-12/2008. Despite center diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 33 publications
5
38
4
1
Order By: Relevance
“…While previous studies have observed an association of CDI with the development of acute GVHD (aGVHD), and increased risk of gastrointestinal aGVHD, 5 this finding has not been consistent. It has been postulated that CDI may represent the initial insult that stimulates the immune response against the gastrointestinal tract.…”
contrasting
confidence: 60%
“…While previous studies have observed an association of CDI with the development of acute GVHD (aGVHD), and increased risk of gastrointestinal aGVHD, 5 this finding has not been consistent. It has been postulated that CDI may represent the initial insult that stimulates the immune response against the gastrointestinal tract.…”
contrasting
confidence: 60%
“…There was a non-significant increase from 3% to 7% in the incidence of C. difficile infection rates after initiating levofloxacin prophylaxis in patients with myeloma that was not seen in patients with lymphoma. Although fluoroquinolones are risk factors for C. difficile infection [21, 22], it is possible that lower rates of bacteremia and FN led to less exposure to other antimicrobial agents, which in turn mitigated the effect of fluoroquinolone prophylaxis on rates of C. difficile infection. As with antimicrobial resistance, monitoring for increased rates of C. difficile infection is warranted with the use of levofloxacin prophylaxis, particularly given the emergence of virulent NAP1 strains that are fluoroquinolone-resistant [10].…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplantation (HSCT) confers increased risk for CDI because of prolonged hospital stay, immunosuppression, the need to use broad-spectrum antibiotics and a complex interplay of chemo-preparative regimen and GvHD-induced gut mucosal damage. The incidence of CDI following autologous and allogeneic HSCT ranges from 5 to 20% [1][2][3][4][5][6][7][8] and recurrence rate has been~20%; 1 consistent with the general population. There are numerous studies describing the epidemiology and risk factors (RFs) of recurrent CDI in the general population, namely receipt of antibiotics, age 460 years, length of hospital stay and concomitant receipt of antacid medications.…”
Section: Introductionmentioning
confidence: 99%